The Influence of Financial Literacy and Financial Attitude on Financial Management of Generation Z in Suli District - Azila, Nur; Hapid, Hapid; Bachri, Samsul (Journal of Applied Business, Taxation and Economics Research, 2025)
Scale used is the Likert scale. The data analysis used is SPSS 30 static analysis and all variable hypotheses Generation Z is a generation group that was born and grew up in the digital era and has unique characteristics compared to previous generations. They are known as "digital natives", which means they have been familiar with the internet, social media and modern technology since childhood. This research aims to determine the influence of financial literacy and financial attitudes on the financial management of Generation Z in Suli District. The population of this study is the population in this study, namely Generation Z in the sub-district, numbering 1,473. The number of samples used was 94 people from a total of 1,473 people surveyed using the Slovin formula. The measurement are accepted and can be stated to have a direct positive and significant effect.